Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Therefore the solution of the equations could be the result of using substitution is 2[tex]y^{2}[/tex]-6 -y=0
What is equation?
In English, an equation is defined as a properly written formula that consists of two expressions joined by an equals sign, while cognates of the word in other languages may have slightly different meanings. For instance, in French, the word "équation" means "thing with one or more variables."
Given two equations are
x=[tex]y^{2}[/tex]-1 and 2x-y=4
We must select an equation from the list of possibilities that may be obtained by utilizing substitution to resolve the problem.
We substitute x in terms of y because the supplied equation is in terms of y.
From 2x-y=4
x=4+y/2
Substitute x=4+y/2 in other equation
We get,
=> x=[tex]y^{2}[/tex]-1
=> 4+y/2 =[tex]y^{2}[/tex]-1
=>4+y=2[tex]y^{2}[/tex]-2
=>2[tex]y^{2}[/tex]-6 -y=0
Therefore the solution of the equations could be the result of using substitution is 2[tex]y^{2}[/tex]-6 -y=0
To know more about equation , visit
https://brainly.com/question/12788590
#SPJ4
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.